Does It Pay to Rebrand? The Relationship Between Corporate Rebranding Strategies and Financial Performance of Joint-Stock Companies. - Natalia K. WOJCIECHOWSKA (Communications of International Proceedings, 2021)
Purpose: The aim of this paper is to examine the relationship between corporate rebranding strategies and companies’ financial performance. Methodology: The sample comprised of 121 joint-stock companies listed on Warsaw Stock Exchange Main Market and New Connect in Poland. The multiple regression was conducted first for corporate rebranding strategies and performance only, and then including the interaction effects of companies’ industry, number of employees and capital structure. Relative growth of profitability indices was calculated with chain base method. Findings: The study partly confirmed that corporate rebranding is positively associated with better financial performance of companies. It also partly confirmed positive moderation of this relationship by both companies’ industry and capital structure. Yet positive moderation of this relationship was not confirmed by the companies’ size. It has been also proved that such rebranding motives as mergers and strategic factors were also positively associated with companies’ financial performance. Research & Practical Limitations/Implications: The study included only four types of corporate rebranding strategies and profitability indices. Corporate brand name extension is positively associated with the largest number of higher profitability indices of all strategies: ROA, ROI, ROE and net profit. Total name change and co-branding are both positively associated with higher ROI. The former is also positively related to net profit, and the latter to sales revenue. Originality/value: The research is one of a few publications which analyze corporate rebranding strategies and financial performance of companies, especially those listed on stock-exchanges. The author did not identify such a research in the Central and Eastern Europe.
Keywords: Financial Performance; Corporate Rebranding; Joint-Stock Company; Relative Growth